Best Answer

4x -2 = 0 First you must balance out the equation and get 'x' all by itself. Add 2 to both sides of the equations: 4x = 2 (The 2's cancel on the left side, -2 +2 equals 0. 0 +2 equals two on the right side) Now you must divide both sides by 4 in order to get 'x' all by itself. x = 2/4 (4 divided by 4 on the left side equals 1. Which leaves 'x' by itself. 2 dived by 4 equals 1/2 or one half) So the solution for 4x -2 = 0 is; x = 1/2

Q: What is this math problem answer 4x-2 equals 0?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

4x2-2x = 0 2x(2x-1) = 0 x = 0 or x =1/2

4x2 - 2x = 0

4x2+50x = 0 4x(x+12.5) = 0 x = 0 or x = -12.5

The first equality is: x2 - 5 = -4x2 which gives 5x2 - 5 = 0 which is equivalent to x2 - 5 = 0 The second equality is: -4x2 = 3x which gives 4x2 + 3x = 0 The two results are inconsistent.

4x2 - 13 x + 3 = 0 (4x - 1)(x - 3) = 0 x = 3, 1/4

Related questions

4x2-2x = 0 2x(2x-1) = 0 x = 0 or x =1/2

4x2 - 2x = 0

4x2+50x = 0 4x(x+12.5) = 0 x = 0 or x = -12.5

There are four solutions to 9x4 plus 27x3 - 4x2 - 12x equals 0. One of the solutions is x = -3.

Assuming that 4x2+2x = 0: 2x (2x+1) = 0 2x = 0 or 2x+1 = 0 x = 0 or -1/2

4x2 = -12x, divide both sides by 4x: x = -3

4x2 - 2x - 3 = 0 (2x + 1)(2x - 3) = 0 x = -(1/2) or (3/2)

x2-5-4x2+3x = 0 -3x2+3x-5 = 0 or as 3x2-3x+5 = 0

The first equality is: x2 - 5 = -4x2 which gives 5x2 - 5 = 0 which is equivalent to x2 - 5 = 0 The second equality is: -4x2 = 3x which gives 4x2 + 3x = 0 The two results are inconsistent.

4x2-4x-3 = 0 (2x-3)(2x+1) = 0 x = 3/2 or x = -1/2

4x2 - 13 x + 3 = 0 (4x - 1)(x - 3) = 0 x = 3, 1/4

(2x - 3)*(4x2 + 6x + 9) = 0